Facial recognition: solution or potentializing old issues? - Ferreira de Albuquerque Costa, Rafael (2024)
This essay aims to analyze the application of new technologies, especially artificial intelligence software developed for facial recognition, to criticize domestic security and the law community’s enthusiasm toward its results through literature review and case law research. For this purpose, we draft a comment about photographic recognition and its jurisprudence correlated to facial recognition dynamics. Then, we discuss the software’s programmatic procedures, the recognition accuracy, and, finally, if there is any efficiency enhancement of criminal prosecution.